2017
DOI: 10.1111/eip.12466
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal ideation and burnout among psychiatric trainees in Japan

Abstract: Our results suggest a higher risk of suicide among Japanese residents. Japan has a higher suicide rate than other countries. Early detection of, and appropriate intervention for, suicidal ideation is important in preventing suicide in psychiatry residents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
1
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 9 publications
1
26
1
1
Order By: Relevance
“…Given that emotional difficulties may arise as a consequence of the challenges of the training environment [16,17], it is imperative that difficulties are addressed early to reduce the negative impact of burnout and depression as one progresses through their career. The training period can be therefore considered a critical time of intervention with regard to the overall well-being and satisfaction of this group.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Given that emotional difficulties may arise as a consequence of the challenges of the training environment [16,17], it is imperative that difficulties are addressed early to reduce the negative impact of burnout and depression as one progresses through their career. The training period can be therefore considered a critical time of intervention with regard to the overall well-being and satisfaction of this group.…”
mentioning
confidence: 99%
“…Stressful trainee experiences were further exacerbated by trainees feeling "underequipped, overwhelmed, or out of time," and importantly, the authors observed that the level of stress experienced by trainees was compounded by lack of supervision [16]. Worryingly, burnout in psychiatry trainees has also been associated with an increased risk of suicidal ideation [17]. It is essential that training bodies be vigilant to these areas to ensure negative trainee experiences are addressed.…”
mentioning
confidence: 99%
“…Studies on burnout and depressive have shown that their relationship is controversial and have provided convincing arguments for all sides of the issue [32][33][34][35]. Some scholars believe that burnout and depression are not isomorphic [32].…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, in our survey, program directors reported needs for lectures and funding, but the priority of protected time was low. Considering the high proportion of burnout in doctors, including residents (18), the Japanese Ministry of Health, Labour and Welfare is now attempting to reform doctors’ working practices in order to reduce their burden (19). Under pressure to lessen work hours, it is important for residents to make progress in their career while prioritizing their time wisely.…”
Section: Discussionmentioning
confidence: 99%